Efektivitas Antibakteri Krim Ekstrak Daun Sirih Merah (Piper crocatum) Terhadap Beberapa Bakteri - Renaldy, Renaldy; Trinovita, Elsa; Furtuna, Dewi Klarita; Fatmaria, Fatmaria; Turnip, Oktaviani Naulita (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
The prevalence of infectious diseases is increasing in developing countries such as Indonesia, and they have become a health problem. One infectious disease caused by Staphylococcus aureus and Escherichia coli bacteria is necrotizing fasciitis. The subcutaneous tissues and fascia necrosis characterize necrotizing fasciitis. Antibiotic therapy is one way to prevent the growth and development of bacteria, but continuous use can cause resistance to bacteria. This research aimed to determine the antibacterial effectiveness of red betel leaf extract in cream preparations against the growth activity of Staphylococcus aureus and Escherichia coli bacteria using the ditch plate method. Red betel leaves were extracted using the UAE method (temperature 600 C for 15 minutes), then made into a cream dosage form with a formulation of 20% extract concentration (F1), 40% extract concentration (F2), and 80% extract concentration (F3) then tested evaluation of cream preparations and antibacterial activity test using the ditch plate method. The extraction of red betel leaves used the UAE method in concentrations of 20%(F1), concentrations of 40%(F2), and concentrations of 80% (F3) in cream preparation form. The cream was evaluated, and antibacterial activity was tested using the ditch plate method. The red betel leaf extract cream inhibits Staphylococcus aureus growth by the ditch plate method but does not have antibacterial activity on Escherichia coli.